Current Evidence and Advances in CAD-CAM Resin Composite Blocks for Chairside Dental Restorations: Where Are We Now? A Scoping Review - Sami Abu Alhuda; Guilherme Anziliero Arossi; Fotini Anagnostopoulos-King; Qoot Alkhubaizi; Lamia S. Mokeem; Mary Anne Sampaio de Melo (Applied Sciences)
Objective: This study aimed to determine the status of the scientific literature on CAD-CAM resin blocks by mapping the available evidence and identifying knowledge gaps. Data/Source: A systematic search of studies investigating CAD-CAM resin blocks was conducted. Risk of bias was assessed, and data on study designs, level of evidence, compositional classification, manufacturer, commercial brand, and properties investigated were extracted. This review followed Arksey and O’Malley’s five-stage framework and utilized Medline (OVID), EMBASE, and Scopus (Elsevier) databases. Study Selection: Study selection resulted in 27 studies for data extraction out of 209 studies screened from an initial pool of 529 studies. High sampling bias related to sample size and randomization was observed in almost all studies. Most studies (99%) were conducted in vitro, with low levels of evidence. The most common composition was “nano-ceramic”. 3M ESPE was the manufacturer with the most investigated blocks, and their product, 3M™ Lava™ Ultimate Restorative, was predominant in the selected investigations. Methodological heterogeneity was extensive among the studies, with mechanical properties (38%) and bond strength (35%) being the most commonly investigated outcomes. Conclusion: This scoping review indicates an increasing trend in dental research assessing CAD-CAM resin blocks. However, the overall level of evidence derived from these studies is low, predominantly consisting of in vitro investigations. Clinical Significance: The findings underscore the need for clinical trials to augment the level of evidence and enable long-term assessment of CAD-CAM resin blocks. Dentists should be cautious while interpreting the findings from in vitro studies, as the outcomes may not directly translate to clinical success.